FAKTOR-FAKTOR BERHUBUNGAN DENGAN PEMILIHAN METODE KONTRASEPSI PADA WANITA AKSEPTOR KB DI WILAYAH KERJA PUSKESMAS JALAN EMAS KABUPATEN TANGERANG TAHUN 2020 - Fanira Cahyaningtyas (2021)
Based on BKKBN 2015, the percentage of contraceptive use (Contraceptive Prevalence Rate/CPR) in Indonesia is 93.4%. Tangerang District Health Profile in 2018 noted that the contraceptive method at Jalan Emas Community Health Center with active Long-term contraception method participants was 14.6% and Non Long-term contraception method was 85.4%. This is related to the increase the total number of births in Tangerang Regency in 2018 up to 74.987 births. Female acceptors are very important about choosing the contraceptive methods. The purpose of this study was to analyze the factors associated with the choice of contraceptive methods for female acceptors in the work area of the Jalan Emas Community Health Center. The research design used in this study was cross sectional. The sampling technique used was cluster sampling and proportionate random sampling. This research was conducted in January 2021 with a total sample 330 female acceptors. The results of statistical tests with chi square showed that there was a significant relationship between the level of basic education (p-value=0,000), lack of knowledge (p-value=0,034), completeness of family planning services (p-value=0,001), exposure to family planning information (p-value=0,036), and access to family planning services (p-value=0,022) on the choice of contraceptive methods among female acceptors. It is hoped that female acceptors can increase insight and correct information about benefits and effectiveness of contraceptive use to increase female acceptors participation in use of long-term contraceptive methods or MKJP.